Me Tri virus: a Semliki Forest virus strain from Vietnam? - Tan, L; Ha, D; Hien, V; van der Hoek, L; Farrar, J; Jong, d (2008)
Me Tri virus (MTV) is a member of the Semliki Forest virus (SFV) complex in the genus Alphavirus, first isolated from Culex tritaeniorhynchus mosquitoes in Vietnam in 1971 and described as a newly recognized alphavirus, based on antigenic characterization. However, based on a partial nucleotide sequence of the E1 envelope glycoprotein gene, it has recently been argued that MTV may represent a variant of SFV rather than a separate species. To enable definitive classification, we determined the complete genome sequence of MTV from original virus stock. Nucleotide homology, as well as phylogenetic analyses based on whole and partial genome sequences confirmed that MTV is an isolate of SFV. Notable differences to other reported SFV sequences included a 122 nt insertion at the 5' non-translated region (NTR), likely resulting from homologous recombination of part of the nsP2 gene, and differences in the sequence length of the 3' NTR. To our knowledge, this is the first and only documentation of SFV isolation outside Africa. Further research is needed to clarify whether SFV continues to circulate in Vietnam.